Steel material and coating formation method
A crystalline FeS layer on steel surfaces addresses hydrogen diffusion and intrusion by converting hydrogen atoms into gas, enhancing the material's resistance to embrittlement and ensuring structural integrity.
Patent Information
- Application Number
- JP2023004112
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-01-26
- Filing Date
- 2023-01-13
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2043-01-13
AI Technical Summary
Existing technologies fail to effectively suppress the diffusion and intrusion of hydrogen into steel materials, particularly in environments where hydrogen is present, leading to delayed fracture and hydrogen embrittlement, which hinders the strengthening of steel components.
A steel material with a crystalline FeS layer on its surface, formed through specific methods, suppresses hydrogen diffusion and intrusion by converting hydrogen atoms into hydrogen gas, effectively discharging them outside the material.
The crystalline FeS layer effectively prevents hydrogen from entering the steel and discharges any hydrogen already present, enhancing the material's resistance to hydrogen embrittlement and promoting structural integrity.
Smart Images

Figure 0007619381000007 
Figure 0007619381000008 
Figure 0007619381000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an iron or steel material, in particular an iron or steel material made of iron or steel, having a coating that can suppress the penetration of hydrogen into the iron or steel material from the environment in which the iron or steel material is used and can discharge hydrogen from the iron or steel material to the outside of the iron or steel material, and to a method for forming the coating on the surface of the iron or steel material. Here, the term "steel material" refers to steel products and parts made of pure iron with an Fe matrix or iron alloys containing alloying elements. This includes not only Cubic ferrite phase, but also Face Centered Cubic austenite phase (such as austenitic stainless steel). This steel product or part includes all products made of pure iron with an Fe parent phase or iron alloys containing alloying elements, such as plate, tube, screw, and gear shapes. [Background technology]
[0002] In recent years, due to concerns about the depletion of resources used in steel manufacturing, there has been active activity to make steel parts lighter and thinner. In order to make parts lighter, it is necessary to increase the strength of the steel materials that are used. However, there is a major obstacle to increasing the strength of steel materials: delayed fracture. It goes without saying that the cause of delayed fracture is a form of so-called hydrogen embrittlement, which is related to hydrogen that penetrates into the steel during the manufacturing process or from the usage environment. However, hydrogen atoms have the simplest and smallest atomic structure, and are the most familiar element that is found all around us as hydrogen gas and compounds with other elements, so it is not easy to prevent their penetration into materials.
[0003] In response to this, the technology described in Patent Document 1 discloses a hydrogen absorption suppression treatment method in which steel material having a resin coating on the surface is intentionally exposed to hydrogen sulfide to form an iron sulfide layer between the coating and the steel material. The iron sulfide layer suppresses the corrosive reaction of hydrogen sulfide to the steel and inhibits hydrogen from penetrating into the steel, thereby preventing stress corrosion cracking, which is a form of hydrogen embrittlement in a hydrogen sulfide environment. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 60-89579 Summary of the Invention [Problem to be solved by the invention]
[0005] The essence of the technology described in the above Patent Document 1 is a technology to suppress the corrosion reaction between iron and hydrogen sulfide, which inevitably accompanies hydrogen generation, but is not a technology to suppress the diffusion and penetration of hydrogen generated by the corrosion reaction into steel itself. In fact, even in Example 7, in which the technology described in Patent Document 1 shows the highest hydrogen absorption suppression ability, the current value increases after a certain period of time in the hydrogen extraction current measurement (Figure 2) after the hydrogen penetration suppression treatment for some reason. This means that hydrogen diffuses through the iron sulfide layer and steel and reaches the surface on the hydrogen extraction side. Thus, with the technology described in Patent Document 1, it is difficult to suppress the diffusion and penetration of hydrogen into the part itself when the part is exposed to hydrogen gas or moisture and hydrogen is generated on the part surface.
[0006] The present invention aims to provide a steel material having a coating on its surface that suppresses the diffusion and intrusion of hydrogen into the steel material itself and enables hydrogen in the steel material to be discharged to the outside, and a method for forming the coating on the surface of the steel material. [Means for solving the problem]
[0007] The present inventors have conducted extensive research to solve the above problems and have come to the following findings. (1) When a coating of iron sulfide (FeS) formed on the surface of steel materials due to corrosion reactions is held at a temperature above 60°C for 15 hours or more, it becomes FeS with a crystalline structure. There are three types of FeS with this type of crystalline structure: Mackinawite, Troilite, and Pyrrhotite.
[0008] (2) Hydrogen does not penetrate from the outside into steel materials having an FeS layer with the above-mentioned crystal structure on the surface.
[0009] (3) Hydrogen atoms originally contained in the steel material having an FeS layer with the above-mentioned crystal structure on its surface are discharged to the outside as hydrogen gas by the FeS layer. Note that the discharge here does not mean natural diffusion of hydrogen by free diffusion, but discharge by the mechanism of the FeS layer with a crystal structure. In other words, the FeS layer with a crystal structure has the function of discharging hydrogen atoms originally contained in the steel material as hydrogen gas, even in an environment where the steel material is exposed to high-pressure hydrogen gas, for example.
[0010] (4) In order for the FeS layer, which has a crystalline structure and exists on the surface of steel materials, to continue to exert its effect of stably suppressing the diffusion and penetration of hydrogen, the thickness of the FeS layer needs to be 1 μm or more.
[0011] (5) Among the three types of FeS with crystalline structures (mackinawite, troilite, and puroite), mackinawite has the highest effect of suppressing the diffusion and penetration of hydrogen.
[0012] Here, the experimental results from which the above findings were obtained will be described in detail. That is, the inventor first immersed a steel bar conforming to JIS G3137 D type 1, which is a typical example of steel material (hereinafter simply referred to as steel bar) in a 20 mass% ammonium thiocyanate solution at 61°C, and which was tempered to a 1400 MPa level. The inventor then performed the presence or absence of a corrosion film formed on the steel surface and the identification of the film, and investigated the immersion time dependency of the corrosion weight loss after the corrosion film was removed and the amount of diffusible hydrogen in the steel at each immersion time. The corrosion weight loss after the corrosion film was removed is the difference between the weight of the test piece (steel material) before immersion and the weight of the test piece (steel material) after immersion, in which the corrosion film formed by immersion was removed by rust removal. The rust removal was performed in accordance with the chemical cleaning method described in the section on the measurement of corrosion weight loss in JIS Z2371. That is, hexamethylenetetramine (C 6 H 12 N 4 The steel was then immersed in a solution containing 3.5 g of hydrogen peroxide at 23°C ± 2°C for 10 minutes to remove rust. The amount of diffusible hydrogen in steel is the cumulative amount (total amount) of hydrogen released from the steel when it is heated from room temperature to 300°C at a heating rate of 0.0278°C / s.
[0013] As shown in Figure 1, the results of the above investigation revealed that, when the condition described in (1) above of immersion for 15 hours or more is met, the hydrogen that once diffused into the steel immediately after the start of immersion decreases after 15 hours of immersion, even though corrosion weight loss continues. It was separately confirmed that the decrease in hydrogen amount due to the change in the aqueous solution was less than 0.5 massppm.
[0014] The film on the steel surface at 15 hours of immersion, when the amount of diffusible hydrogen changes from an increase to a decrease, was identified by thin-film X-ray diffraction, and it was found that FeS with crystalline structures such as mackinawite, troilite, and puroite had formed. Measurement of the thickness of the FeS layer with crystalline structure that formed on the surface during immersion using a scanning electron microscope revealed that the amount of hydrogen in the steel began to decrease when the layer reached a thickness of approximately 1 μm or more. Furthermore, the thickness of the FeS layer with crystalline structure continued to increase during immersion, which meant that the corrosion reaction continued during immersion, and this was confirmed not only by the corrosion weight loss results but also visually.
[0015] On the other hand, when the coating on the steel surface was identified by thin-film X-ray diffraction at the 14-hour immersion time point, when the amount of diffusible hydrogen was increasing, only Fe peaks were observed, and no diffraction peaks corresponding to FeS (mackinawite, troilite, or puroite) were observed. From this, it was inferred that even if iron and sulfur compounds were obtained at immersion times of less than 15 hours, they would remain in an amorphous state without a crystalline structure, and would therefore not have the functionality that FeS with a crystalline structure would exhibit.
[0016] From these results, it was inferred that the reduction of hydrogen that had once penetrated into the steel during the initial immersion period was related to the FeS layer, which has a crystalline structure and is a product of the corrosion reaction.
[0017] Next, in order to verify where the hydrogen content in the steel that decreased after 15 hours, when the hydrogen content in the steel started to decrease, went in the test piece (steel) with the FeS layer having a crystalline structure, the hydrogen temperature rise curves of the steel after immersion with the FeS layer having a crystalline structure and the steel after removing the FeS layer from the surface under the same immersion conditions were compared. Here, the hydrogen temperature rise curve is a curve obtained by plotting the amount of hydrogen released from the steel at the temperature when the test piece (steel) is heated, with the temperature on the horizontal axis. This hydrogen temperature rise curve makes it possible to grasp the amount of hydrogen released from the test piece at what temperature, and by comparing the temperature corresponding to the peak of the curve and the amount of hydrogen released at that time, it is possible to infer the state of hydrogen in the steel. In this study, by comparing the shape of this hydrogen temperature rise curve with the amount of hydrogen released at the peak, it was inferred whether the amount of hydrogen in the steel was absorbed in the FeS layer having a crystalline structure.
[0018] As a result of the above comparison, no significant differences were found in the shape of the hydrogen temperature rise curve or the position of the hydrogen release peak with or without the FeS layer, so it was concluded that the reduced hydrogen in the steel was not stored in the FeS layer but was released into the solution. Because the corrosion reaction accompanied by hydrogen generation continued even while the amount of hydrogen in the steel was decreasing, the steel immersed in the aqueous solution was exposed to an environment in which hydrogen could diffuse into the steel, yet hydrogen in the steel was released into the solution. This led to the conclusion that the FeS layer, which has a crystalline structure, has the function of preventing hydrogen from penetrating from the outside and of expelling hydrogen that had once penetrated the steel to the outside.
[0019] Furthermore, after extensive research into why the crystalline FeS layer has such functionality, the researchers concluded that this is because the hydrogen overvoltage is small on the free surface of the crystalline FeS layer. The low hydrogen overvoltage means that hydrogen atoms that have become adsorbed hydrogen atoms through the Volmer reaction on the surface of the crystalline FeS layer bond with each other to form hydrogen gas (H 2) is small. On the other hand, hydrogen overvoltage corresponds to the deviation of the chemical energy of the adsorbed hydrogen atoms from the equilibrium state, and the free surface of the FeS layer, which has a crystal structure with a small hydrogen overvoltage, also has a lower chemical potential because it approaches equilibrium. The driving force for the diffusion of a substance is the gradient of the chemical potential, so as the chemical potential of the free surface of the FeS layer, which has a crystal structure with a lowered chemical potential as described above, a driving force for hydrogen diffusion is generated as the chemical potential decreases, and the hydrogen in the steel diffuses to the free surface of the FeS layer, which has a crystal structure, becomes adsorbed hydrogen at the free surface, and is then released outside the steel as hydrogen gas. The above is the mechanism by which the FeS layer having a crystalline structure suppresses hydrogen penetration and at the same time expels hydrogen from the steel to the outside.
[0020] Furthermore, the researchers investigated the effect of each of the crystalline FeS species, mackinawite, puroite, and troilite, in suppressing the diffusion and penetration of hydrogen into steel. As a result, they found that the effect was greatest when an FeS layer in which only the mackinawite peak appeared was obtained in thin-film X-ray diffraction analysis.
[0021] Based on the above findings, the inventor has completed the present invention. That is, the gist and configuration of the present invention are as follows. 1. A steel material having a crystalline FeS layer on its surface that is 1 μm or more thick.
[0022] 2. Specific liquid volume is 10ml / cm 2 A method for forming a coating in which a steel material is immersed in an aqueous solution of ammonium thiocyanate with a concentration of 1 mass% or more, which is kept at a temperature of 100°C or higher and over 60°C, for 15 hours or more.
[0023] 3. Specific liquid volume is 10ml / cm 2 and above 60℃, 2 A method of forming a coating in which steel materials are immersed in an aqueous solution containing 1 massppm or more of S for 15 hours or more.
[0024] 4. Relative humidity is kept above 90% and above 60°C.2 A method of forming a coating in which steel materials are exposed to an atmosphere containing 1 massppm or more of S for 15 hours or more.
[0025] 5. Specific liquid volume is 10ml / cm 2 The steel material is immersed in ion-exchanged water maintained at a temperature of 60°C or higher, and pure H is added to the ion-exchanged water in which the steel material is immersed. 2 A method of forming a coating by continuously blowing in S gas for more than 15 hours. Effect of the Invention
[0026] According to the present invention, it is possible to suppress the intrusion of hydrogen from the usage environment into the steel material, and to expel hydrogen originally present in the steel material to the outside of the steel material. Furthermore, according to the method of the present invention, it is possible to form a coating that functions as described above on the surface of the steel material. [Brief description of the drawings]
[0027] [Figure 1] 1 is a graph showing the transition of the amount of diffusible hydrogen in steel and the transition of corrosion weight loss when a steel material is immersed in a corrosive solution. [Diagram 2] 1A and 1B are diagrams illustrating a method for determining an angle at which a peak exists from an X-ray spectrum. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] The present invention will be specifically described below. The steel material of the present invention has, on its surface, an FeS layer having a crystal structure with a thickness of 1 μm or more.
[0029] [FeS layer thickness: 1μm or more] The thickness of the FeS layer is the thickness of the layer in the cross-sectional direction of the steel material. When the cross-sectional thickness of the FeS layer formed on the surface of the steel material is 1 μm or more, the FeS layer coating exhibits the function of suppressing hydrogen penetration. It is more preferably 1.5 μm or more. On the other hand, there is no particular need to limit the upper limit of the thickness, but from the viewpoint of adhesion of the FeS layer to the steel material (base material), it is preferably 500 μm or less. It is more preferably 300 μm or less.
[0030] Whether or not the FeS layer has a crystalline structure is determined by thin film X-ray diffraction. FeS with a crystalline structure can be classified into the following three types: <Mackinawight> Mackinawite is a mineral in which sulfur and iron are bonded by ionic bonds in a ratio slightly richer in iron than the stoichiometric ratio of 1:1. The crystal structure is tetragonal. This crystal structure can be identified by X-ray diffraction.
[0031] <Troy Light> Troilite is a mineral composed of sulfur and iron bonded by ionic bonds in a stoichiometric ratio of 1:1. Its crystal structure is hexagonal. This crystal structure can be identified by X-ray diffraction.
[0032] <Purotite> Pyrrhotite is a mineral in which sulfur and iron are bonded by ionic bonds in a ratio slightly richer than the stoichiometric ratio of 1:1. The crystal structure is monoclinic. This crystal structure can be identified by X-ray diffraction.
[0033] Next, a method for determining whether or not FeS having the above-mentioned crystal structure is present by X-ray diffraction will be described. A test piece taken from the steel material on which the coating was formed is analyzed using a commercially available thin-film X-ray diffractometer, and X-ray diffraction results are obtained for detector angles up to 90° from the incidence angle of the X-rays on the test piece. The X-ray source is CuKα radiation. From the spectrum of X-ray intensity detected by the detector versus the detector angle of the diffracted X-rays obtained in this way, all detector angles at which peaks exist are determined, and a group of peaks in the test piece is obtained. The group of peaks obtained is compared with the peak groups of mackinawite, troilite, and puroite provided by the ICDD (International Center for Diffraction Data), and if there are three or more peak angles that match any of the three types of substances mentioned above, it is determined that any of the three types of FeS is present.
[0034] Here, the criterion for determining whether the peak positions match is that if the measured peak is within ±1° of the peak position provided by the ICDD, it is determined that the peak positions match.
[0035] Furthermore, a method for determining the angle at which a peak exists from the X-ray spectrum of the measurement results will be described with reference to Figure 2. First, the minimum value of the X-ray intensity (hereinafter referred to as "X-ray intensity Y") existing within ±5° (A°±5°) of a certain angle (hereinafter referred to as "A°") in the spectrum of X-ray intensity versus detector angle is obtained. By collecting A° where the X-ray intensity at A° is at least twice the X-ray intensity Y, an A° with a certain width for one peak is obtained. The median angle of this width is determined to be the angle at which the peak exists.
[0036] [Coating] As described above, the steel material of the present invention is characterized in that it has an FeS layer with a crystal structure of 1 μm or more on the surface. Here, having an FeS layer with a crystal structure of 1 μm or more on the surface of the steel material means that a coating of a crystalline FeS layer with a thickness of 1 μm or more is exposed to the outside world between the steel material and the outside world. The outside world refers to the solution, gas, or solid with which the steel material is in contact, that is, the so-called external environment. However, as for the film as a whole, it is acceptable for other types of Fe and S compound layers, such as <greigite>, <smythite>, <pyrite>, or <marcasite>, to exist between the FeS layer and the steel material (base material). However, even in this case, the layer in contact with the outside environment, that is, the outermost layer of the film that is exposed to the outside environment, needs to be an FeS layer that has a crystal structure and is 1 μm or more thick from the viewpoint of the above-mentioned hydrogen overvoltage. When there is a layer of a compound other than FeS, such as greigite, between the FeS layer having a crystalline structure and the steel material (base material), there is no particular limit to the thickness of the compound layer. However, if the thickness of this compound layer exceeds 1 mm, the adhesion to the base steel material decreases significantly, so it is preferably 1 mm or less, more preferably 500 μm or less.
[0037] The above-mentioned greigite has the chemical formula Fe 3 S 4 It is a mineral of Fe and S bonded by ionic bonds and has a cubic crystal structure. The above smysite has the chemical formula Fe 3 S 4 It is a mineral of Fe and S bonded by ionic bonds, and has a hexagonal crystal structure. The above pyrite has the chemical formula FeS 2 It is a mineral of Fe and S bonded by ionic bonds, and has a cubic crystal structure. The above marcasite has the chemical formula FeS 2 It is a mineral of Fe and S bonded by ionic bonds, and has a rectangular crystal structure.
[0038] Next, a method for forming a coating for producing the steel material of the present invention will be described. Specifically, the following methods a to d are advantageously applicable. Formation method A: specific liquid volume 10ml / cm 2 The steel material is immersed in an aqueous solution of ammonium thiocyanate with a concentration of 1 mass% or more, which is kept at a temperature of 100°C or higher and above 60°C, for 15 hours or more. Formation method B: specific liquid volume 10ml / cm 2 and above 60℃, 2 The steel material is immersed in an aqueous solution containing S at 1 massppm or more for 15 hours or more. Formation method c: Relative humidity is kept at 90% or more and above 60°C. 2 The steel material is left standing in an atmosphere containing S at 1 massppm or more for 15 hours or more. Formation method d: specific liquid volume 10ml / cm 2 The steel material is immersed in ion-exchanged water maintained at a temperature of 60°C or higher, and pure H is added to the ion-exchanged water in which the steel material is immersed. 2 S gas is blown continuously for more than 15 hours. Each of the formation methods will be described below in order.
[0039] Formation method a [Ammonium thiocyanate solution with a concentration of 1 mass% or more] In the cathodic reaction of steel materials in an aqueous solution of ammonium thiocyanate, thiocyanic acid (SCN-) decomposes to produce carbon dioxide, ammonium, and S. 2- ions and hydrogen atoms are produced. 2- To obtain this, an aqueous solution containing 1 mass% or more of ammonium thiocyanate is necessary. A more preferred concentration is 2 mass% or more.
[0040] [Specific liquid volume 10ml / cm 2 End] The amount of solution relative to the surface area of the steel material, i.e., the specific liquid volume, is 10ml / cm 2If the specific liquid volume is less than this, the steel material often cannot be immersed to a sufficient depth in the solution. In other words, if the specific liquid volume is less than this, some part of the surface of the steel material will be close to the surface of the solution or will be outside the solution, and as a result, a coating of sufficient thickness will not be obtained at such parts, and the hydrogen penetration suppression effect will not be obtained at such parts. This is also true for the other coating formation methods b and d in which the steel material is immersed in the solution.
[0041] The denominator of the specific liquid volume is the total surface area of the steel material to be immersed, and the numerator is the amount of solution. An aqueous solution is a liquid in which water with a purity similar to that of ion-exchanged water is used as a solvent and some substance is dissolved in it as a solute.
[0042] [Temperature over 60℃] Although a corrosion film of iron sulfide can be obtained even if the temperature of the above aqueous solution is 60°C or lower, the iron sulfide does not become FeS having a crystalline structure. In order to make FeS have a crystalline structure, the temperature of the above aqueous solution must be higher than 60°C. This is the same for all the coating formation methods described below. Once an FeS layer is obtained, as long as this FeS layer is stably present, the mechanism of hydrogen penetration suppression and hydrogen release is expressed even at a temperature of 60°C or lower, that is, near room temperature. The temperature is preferably 61°C or higher, more preferably 65°C or higher. Even more preferably, the temperature is 70°C or higher.
[0043] [Soaking time: 15 hours or more] The immersion time in the above aqueous solution must be 15 hours or more. In other words, if the immersion time is less than 15 hours, an FeS layer having a thickness of 1 μm or more cannot be obtained. More preferably, it is 20 hours or more. This immersion time is the same in the other coating formation method b. Furthermore, the atmospheric exposure time in formation method c and the blowing time in formation method d are also 15 hours or more.
[0044] Formation method b [H 2 Aqueous solution containing 1 massppm or more of S At a concentration of 1 massppm or more, H 2In an aqueous solution containing S, iron or steel undergoes a corrosion reaction to produce iron sulfide, preferably at a concentration of 2 massppm or more. And this H 2 In an aqueous solution containing S, the specific liquid volume is 10 ml / cm 2 By soaking the material in the above conditions at a temperature of 60° C. or higher for 15 hours or longer, a FeS layer having a crystal structure and a thickness of 1 mm or more is formed.
[0045] Formation method c [Relative humidity is 90% or more. 2 [Atmosphere containing 1 massppm or more of S] H at a concentration of 1 massppm or more 2 Even in an atmosphere containing S, iron or steel can produce iron sulfide through a corrosion reaction, but in order to accelerate the corrosion to a certain extent and obtain a uniform corrosion film, the relative humidity must be 90% or higher. The concentration is preferably 2 massppm or higher.
[0046] [H 2 [S] If the time for exposure (standing) in the above atmosphere is less than 15 hours, an FeS layer having a thickness of 1 μm or more cannot be obtained, and it is more preferable that the time is 20 hours or more.
[0047] Formation method d [Ion exchange water is used to immerse steel materials in pure H 2 S gas is continuously injected. Steel materials were immersed in ion-exchanged water and pure H was added to the same ion-exchanged water. 2 By continuously injecting S gas, an iron sulfide coating can be formed on the surface of steel materials. Here, pure H in ion-exchanged water 2 The amount of S gas blown in must be 1 L / min or more per 1 L of ion-exchanged water. 2 S gas is H 2 It refers to a gas with a S concentration of 99% or more, and the gas blown in is pure H. 2 If S gas is not used, a problem occurs in that a crystal structure sufficient for reducing the hydrogen overvoltage cannot be obtained.
[0048] [Pure H 2 S gas is blown continuously for more than 15 hours. Pure H 2 If the S gas is blown into the ion-exchanged water for less than 15 hours, an FeS layer having a thickness of 1 μm or more cannot be obtained, and it is more preferable to blow the S gas into the ion-exchanged water for 20 hours or more. EXAMPLES
[0049] The present invention will be described in more detail below with reference to examples. However, these examples are merely examples, and the present invention is not limited to the following examples. Three types of steel having the chemical compositions shown in Table 1 were melted in a vacuum melting furnace, and 50 kg steel ingots were cast to obtain ingots. Here, Steel No. 1 is a steel with chemical compositions within the range specified for PC steel bars as D-type No. 1 in JIS G 3137, Steel No. 2 is a steel with chemical compositions within the range specified for SCM435 in JIS G 4053, and Steel No. 3 is a steel equivalent to pure iron, known as a base metal.
[0050] [Table 1]
[0051] Next, these ingots were hot worked at a temperature of 1200°C or higher to obtain a cylinder with a diameter of 32 mm. From the cylinder with a diameter of 32 mm, round bars with a diameter of 12 mm and a length of 200 mm were cut out, and for steels No. 1 and 2, the round bars were subjected to a tempering treatment (quenching: soaked at 890°C for 30 minutes, then quenched in an oil bath at 60°C, tempering: soaked at 400°C for 45 minutes, then cooled in an oil bath at 60°C). For steel No. 3, a normalizing treatment was performed (held at 950°C for 1 hour, then air-cooled to room temperature in the air). The Vickers hardness (measured under a load of 10 kgf) of each steel after the tempering treatment or normalizing treatment is also shown in Table 1. From each steel subjected to such tempering treatment, a round bar with a diameter of 8 mm and a length of 30 mm was cut out and subjected to the coating formation treatment shown in Tables 2, 3, 4 and 5.
[0052] First, the coating formation treatment shown in Tables 2 and 3 is carried out by immersing the sample in an aqueous solution of ammonium thiocyanate (method a), 2 Method b: Immersion in S aqueous solution; Method H: 2 Method c: leaving the sample in an S atmosphere (this method is referred to as "leaving the sample in an atmosphere" in Tables 2 and 3); 2 Method d of blowing in S gas (this method is referred to as "H 2 The conditions for each method are shown in Tables 2 and 3.
[0053] In methods a, b, and d, in which the rods were immersed in the solution, two of the above-mentioned 8 mm diameter rods were immersed in each solution. Similarly, in method c, in which the rods were left standing in the atmosphere, two rods were left standing. In each method, the two test pieces (rods) were taken out after the time shown in Tables 2 and 3 had elapsed after immersion in the aqueous solution or standing in the atmosphere. One of the two test pieces thus obtained was first analyzed by a thin-film X-ray diffractometer to determine whether a layer of FeS with a crystalline structure was formed on the surface. The results of this determination are shown in Tables 2 and 3 as "presence or absence of FeS" and "number of coincident peaks." The "number of coincident peaks" refers to the number of peaks that, among the peaks of the test piece obtained by thin-film X-ray diffraction investigated by the thin-film X-ray diffraction method, have angles that coincide with the peaks of mackinawite, troilite, and puroite provided by ICDD. If this number is 3 or more, it means that FeS with the crystalline structure of any of the above three types of FeS has been obtained. After this evaluation, the test pieces were subjected to measurement of the coating thickness.
[0054] For the test pieces used to measure the coating thickness, the test pieces were processed so that a cross section perpendicular to the longitudinal direction of the cylindrical shape (a cross sectional section, or so-called C section) could be observed. After processing, the test pieces were embedded in resin so that the C section would be the observation surface, and then mirror polished. The surface coating thickness was observed using a Scanning Electron Microscopy (commonly known as SEM).
[0055] The remaining test piece was immersed in a 20 mass% ammonium thiocyanate aqueous solution held at 30°C for 48 hours to allow hydrogen to penetrate. This is called "re-immersion", and the test piece immersed in a 20 mass% ammonium thiocyanate aqueous solution held at 30°C for 48 hours after the coating treatment is called the "re-immersed material" in Tables 2 and 3. In addition, at the start of the re-immersion of this coating treatment material, an untreated test piece that had not been treated with coating, that is, an as-processed test piece, was also immersed in the same solution as the re-immersed material, that is, in the same beaker. The test piece immersed together in this as-processed state for 6 hours is called the "newly immersed material" in Tables 2 and 3. The specific liquid volume during this re-immersion was 10 ml / cm 2 The pH of the solution was 6.0 or higher at a measurement temperature of 30°C ± 2°C.
[0056] The amount of hydrogen in the steel of the re-dipped and newly dipped materials was measured using a hydrogen temperature rise analyzer connected to a gas chromatograph in a tube furnace. The carrier gas was Ar gas, and the measurement was performed at a heating rate of 0.0278°C / s. The gas sampling interval was 5 minutes. The test pieces before this analysis were stored at liquid nitrogen temperature, and the analysis was started within 30 minutes after they were removed from the liquid nitrogen and returned to room temperature. Prior to the analysis, the coating on the surface of the test pieces was manually scraped off with #320 dry abrasive paper until a metallic luster was obtained, and then the test pieces were analyzed (this does not apply when analyzing with some FeS layers). Based on the results of this hydrogen temperature rise analysis, the amount of hydrogen in the steel at each temperature was plotted against the temperature to create a hydrogen temperature rise curve. The cumulative amount of hydrogen released from room temperature (start of analysis) to 300°C was taken as the amount of diffusible hydrogen.
[0057] In addition, the coating obtained by the coating formation process was evaluated for its ability to suppress hydrogen penetration and release hydrogen from the steel to the outside (hereinafter referred to as a hydrogen sink film). Test pieces in which the ratio of the diffusible hydrogen content of the re-immersed material to the hydrogen content of the newly immersed material was less than 0.5 were deemed to be test pieces in which the obtained coating functioned sufficiently as a hydrogen sink, that is, the test pieces released hydrogen from the steel during coating formation and re-immersion, and suppressed hydrogen penetration from the outside during these processes and tests.
[0058] In Tables 2 and 3, the comparative specimens No. 1, 2, 17, 18, 39, 40, 53, 61, and 72 had a coating thickness of more than 1 μm obtained by the coating formation process, but because the treatment temperature was below 60°C, a FeS coating with a crystalline structure was not obtained, and sufficient hydrogen sink function was not obtained. Thin-film X-ray diffraction tests were performed on these coatings to attempt to identify the coatings, but no peaks corresponding to mackinawite, troilite, or puroite were obtained. The composition analyzer attached to the SEM confirmed the presence of S in the coating, but as mentioned above, no X-ray diffraction peaks corresponding to the crystal structure of FeS were obtained, so it is presumed that the coating obtained was probably an amorphous FeS coating.
[0059] Furthermore, in the test pieces Nos. 3, 4, 9, 10, 19, 20, 25, 26, 41, 42, 47, 48, 54, 57, 62, 65, 73, and 76 shown in Tables 2 and 3, which are comparative examples, a layer of FeS having a crystalline structure was obtained, but the thickness of the coating obtained by the coating formation process was less than 1 μm, so that the test pieces did not exhibit sufficient function as hydrogen sinks.
[0060] The test pieces in Tables 2 and 3 other than the above comparative examples, i.e., test pieces Nos. 5, 6, 7, 8, 11, 12, 13, 14, 15, 16, 21, 22, 23, 24, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 43, 44, 45, 46, 49, 50, 51, 52, 55, 56, 58, 59, 60, 63, 64, 66, 67, 68, 69, 70, 71, 74, 75, 77, and 78, are invention examples that satisfy the present invention.
[0061] [Table 2]
[0062] [Table 3]
[0063] Table 4 also shows the results of the test pieces treated under the preferred treatment conditions described in Patent Document 1. As for the type of coating resin prior to the coating treatment in Table 4, since it was difficult to reproduce all conditions, only one condition was used, that of an epoxy resin with a film thickness of 5 μm (curing conditions: drying at room temperature for 10 days). A round bar having such a coating was treated under the conditions shown in Table 3, and the hydrogen amounts of the re-immersed material and the newly immersed material were compared. As a result, none of the test pieces exhibited sufficient hydrogen sink function. The hydrogen amount of the newly immersed material was significantly smaller than the value in Table 2, but this is presumably because the epoxy coating formed prior to immersion suppressed the corrosion reaction to some extent in the 20 mass% ammonium hydrogen thiocyanate solution. In any case, it is clear that the function as a hydrogen sink evaluated as the ratio of the re-immersed material to the newly immersed material is not sufficiently obtained.
[0064] [Table 4]
[0065] Furthermore, Table 5 shows the results of the example shown in Table 1 of Patent Document 1, in which the temperature was kept constant in an atmosphere and H 2 The results are shown for the coating formation treatment method using S gas injection. In Comparative Examples 89, 90, 91, 92, 93, 94, 97, 98, 99, and 100, FeS with a crystalline structure was obtained, but the treatment time was short and a coating exceeding 1 μm was not obtained, so it did not function adequately as a hydrogen sink. In Comparative Examples 95 and 96, the treatment temperature was low, so FeS with a crystalline structure was not obtained, and the treatment time was also short, so a coating of sufficient thickness was not obtained, so it did not function adequately as a hydrogen sink.
[0066] [Table 5]
[0067] Furthermore, Table 6 compares the effect of each type of FeS layer in suppressing hydrogen diffusion penetration for an FeS layer of mackinawite only, an FeS layer of puroite only, and an FeS layer of troilite only. Examples 101 and 102 show the results for a layer of mackinawite only, Examples 103 and 104 show the results for a layer of troilite only, and Examples 105 and 106 show the results for a layer of puroite only. In all layers, the ratio of the diffusible hydrogen amount of the re-soaked material to that of the newly soaked material was less than 0.5. In particular, it is clear that Examples 101 and 102, which obtained layers of mackinawite only, had a significantly smaller hydrogen amount ratio than the other layers.
[0068] [Table 6]
Claims
【Request 1】 Specific liquid volume is 10ml / cm 2 The method for forming a coating film comprises immersing a steel material in an aqueous solution of ammonium thiocyanate having a concentration of 1 mass% or more, the aqueous solution being maintained at a temperature of 100° C. or higher and exceeding 60° C., for 15 hours or more. 【Request 2】 Relative humidity is kept at 90% or more and 60°C or higher. 2 A method for forming a coating, comprising leaving a steel material standing in an atmosphere containing S at 1 ppm by mass or more for 15 hours or more. 【Request 3】 Specific liquid volume is 10 ml / cm 2 The steel material is immersed in ion-exchanged water maintained at a temperature of 60° C. or higher, and pure H is added to the ion-exchanged water in which the steel material is immersed. 2 A method for forming a coating in which S gas is blown continuously for 15 hours or more.
Citation Information
Patent Citations
Sliding member excellent in abrasion resisting property
JP1980011107A
Treatment for suppressing hydrogen absorption of steel material
JP1985089579A
Corrosion resistant carbon steel
JP2000508382A